q-Rung orthopair fuzzy hypersoft ordered aggregation operators and their application towards green supplier - Khan, Salma; Gulistan, Muhammad; Kausar, Nasreen; Pamucar, Dragan; Ozbilge, Ebru; El-Kanj, Nasser (Frontiers in Environmental Science, 2023)
Green supply chain management (GSCM) is essential to ensure environmental compliance and commercial growth in the current climate. Businesses constantly look for fresh concepts and techniques for ensuring environmental sustainability. To keep up with the new trends in environmental concerns related to company management and procedures and, green supplier selection (GSS) criteria are added to the traditional supplier selection processes. This study aims to identify general and environmental supplier selection criteria to provide a framework that can assist decision-makers in choosing and prioritizing appropriate green supplier selection. For this, we investigated expert opinions using the MCDM technique to identify the interrelationship and causal preference of green supplier evaluation aspects using aggregation operators. finally, we present a numerical example of the proposed method for the task of Green supplier selection.